Prediction of fresh and ripened cheese yield using detailed milk composition and udder health indicators from individual Brown Swiss cows - Mariani, Elena; Malacarne, Massimo; Cipolat-Gotet, Claudio; Cecchinato, Alessio; Bittante, Giovanni; Summer, Andrea (Frontiers in Veterinary Science, 2022)
The composition of raw milk is of major importance for dairy products, especially fat, protein, and casein (CN) contents, which are used worldwide in breeding programs for dairy species because of their role in human nutrition and in determining cheese yield (%CY). The aim of the study was to develop formulas based on detailed milk composition to disentangle the role of each milk component on %CY traits. To this end, 1,271 individual milk samples (1.5L/cow) from Brown Swiss cows were processed according to a laboratory model cheese-making procedure. Fresh %CY (%CYCURD), total solids and water retained in the fresh cheese (%CYSOLIDS and %CYWATER), and 60-days ripened cheese (%CYRIPENED) were the reference traits and were used as response variables. Training-testing linear regression modeling was performed: 80% of observations were randomly assigned to the training set, 20% to the validation set, and the procedure was repeated ten times. Four groups of predictive equations were identified, in which different combinations of predictors were tested separately to predict %CY traits: i) basic composition, i.e. fat, protein, and CN, tested individually and in combination; ii) udder health indicators (UHI), i.e. fat + protein or CN + lactose and/or somatic cell score (SCS); iii) detailed protein profile, i.e. fat + protein fractions [CN fractions, whey proteins, and nonprotein nitrogen (NPN) compounds]; iv) detailed protein profile + UHI, i.e. fat + protein fractions + NPN compounds and/or UHI. Aside from the positive effect of fat, protein, and total casein on %CY, our results allowed us to disentangle the role of each casein fraction and whey protein, confirming the central role of β-CN and κ-CN, but also showing α-lactalbumin (α-LA) to have a favorable effect, and β-lactoglobulin (β-LG) a negative effect. Replacing protein or casein with individual milk protein and NPN fractions in the statistical models appreciably increased the validation accuracy of the equations. The cheese industry would benefit from an improvement, through genetic selection, of traits related to cheese yield and this study offers new insights into the quantification of the influence of milk components in composite selection indices with the aim of directly enhancing cheese production.